A contactless probe utilizing inductive coupling. (May 2017) - Ibne Basith, Iftekhar; Jedari, Esrafil; Rashidzadeh, Rashid
Abstract: Contactless probing eliminates many problems associated with direct probing. In this article, a microscale contactless probe is presented which can be used to observe data activity. The proposed contactless probe operates based on the principle of resonant inductive coupling. This coupling method as compared to the conventional inductive coupling technique supports higher efficiency and allows data observation from longer distances. To implement the proposed method just a microscale inductor and a transistor are needed to observe data activity. This will minimize the area overhead. Experimental measurement results on a prototype fabricated in TSMC 65 nm CMOS technology show that the transmitted data can be reconstructed when the distance between the transmitter and the probe remains less than 15 µm.